1984
DOI: 10.1055/s-2007-1017413
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Activity of the Benzodiazepine Antagonist Ro 15-1788 in Man: An Electrophysiological Investigation

Abstract: Ten healthy volunteers were injected i.v. with 5 mg Ro 15-1788, a specific benzodiazepine antagonist, or placebo in a double-blind randomised design. In the EEG, Ro 15-1788 led--with some topographical variations--to a diminution of theta and alpha power, an increase of alpha mean frequency and a decrease of delta mean frequency. In auditory evoked potentials, the N1P2 and P2N2 amplitudes decreased. The electrophysiological changes induced by Ro 15-1788 are consistent with a central stimulant action. Ro 15-178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
2
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 0 publications
6
22
2
1
Order By: Relevance
“…Flumazenil did not affect the risk assessment measures, but it dramatically potentiated flight reactions while weakly, albeit significantly, reducing defensive aggression and contextual anxiety. The effects of flumazenil on flight may well fit with clinical observations that the drug is somewhat anxiogenic in healthy volunteers (Darragh et al, 1983;Duka et al, 1986;Schopf et al, 1984) and that it increases the frequency of panic attacks in panic disorder patients (Maddock, 1998;Nutt et al, 1990;Woods et al, 1991). The weak agonist-like activity of flumazenil on defensive aggression is at first glance surprising, but it may fit with the idea that the drug can produce a GABA A -benzodiazepine receptor set point shift either toward the agonistic or the inverse agonistic direction, depending on the aversiveness of the situation (Belzung et al, 2000).…”
Section: Effects Of Nonselective Gaba a -Benzodiazepine Receptor Ligasupporting
confidence: 70%
“…Flumazenil did not affect the risk assessment measures, but it dramatically potentiated flight reactions while weakly, albeit significantly, reducing defensive aggression and contextual anxiety. The effects of flumazenil on flight may well fit with clinical observations that the drug is somewhat anxiogenic in healthy volunteers (Darragh et al, 1983;Duka et al, 1986;Schopf et al, 1984) and that it increases the frequency of panic attacks in panic disorder patients (Maddock, 1998;Nutt et al, 1990;Woods et al, 1991). The weak agonist-like activity of flumazenil on defensive aggression is at first glance surprising, but it may fit with the idea that the drug can produce a GABA A -benzodiazepine receptor set point shift either toward the agonistic or the inverse agonistic direction, depending on the aversiveness of the situation (Belzung et al, 2000).…”
Section: Effects Of Nonselective Gaba a -Benzodiazepine Receptor Ligasupporting
confidence: 70%
“…imipramine,¯uoxetine, moclobemide and phenelzine), reduced¯ight behavior [12,48,49,51]. In contrast, drug challenges known to trigger or potentiate human panic responses such as acute imipramine,¯uoxetine, yohimbine or the BZ receptor antagonist¯umazenil [27,54,55,90] were found to increase¯ight [16,48]. Also in agreement with clinical data are the ®ndings that the traditional BZ chlordiazepoxide, the 5-HT1A receptor agonist buspirone and the 5-HT2 receptor antagonist mianserin did not modify¯ight behavior in this test [50,52].…”
Section: Panic Disorder (Pd)supporting
confidence: 66%
“…Whereas in some studies (Doenicke et al, 1984, Gath et al, 1984Noderer et al, 1988) no significant changes compared with placebo were reported, Schopf et al (1984) found with 5 mg flumazenil a similar central stimulant action to that described above. Furthermore, Ziegler et al (1985) could demonstrate that flumazenil (10 mg i.v.)…”
Section: Discussionmentioning
confidence: 81%